2016
DOI: 10.1016/j.tox.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of pre and postnatal androgen environments and anogenital distance in rats

Abstract: We examined the anogenital distance (AGD) plasticity in rats through the manipulation of the androgen environment in utero and during puberty. Dams were treated from gestation days 13-20 with vehicle, flutamide (20mg/kg/day), di-(2-ethylhexyl) phthalate (DEHP, 750mg/kg/day), or testosterone (1.0mg/kg/day). After weaning, male pups were randomly assigned to one of four postnatal groups, which received the same treatments given prenatally. Sixteen treatment groups were established based on the combination of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 27 publications
0
18
1
1
Order By: Relevance
“…; Kita et al. ). Alternatively, it could be that the density of males within the postnatal, preweaning maternal environment led to differences in sperm sex ratios.…”
Section: Discussionmentioning
confidence: 97%
“…; Kita et al. ). Alternatively, it could be that the density of males within the postnatal, preweaning maternal environment led to differences in sperm sex ratios.…”
Section: Discussionmentioning
confidence: 97%
“…In a study on rats, animals fed 750 mg kg −1 day −1 between gestation days 13 and 20 showed significant reduction in AGD (P = 0.001). 32 AGD was significantly correlated with penile width (r = 0.31, P < 0.05) and penile length (r = 0.16, P ≈ 0.05). 31 In addition to penile width and length, AGD is also correlated with penile volume.…”
Section: -14mentioning
confidence: 92%
“…The concentrations of phthalate metabolites, including the DEHP metabolites MEHP, mono‐(2‐ethyl‐5‐hydroxyhexyl) phthalate (MEHHP) and mono‐(2‐ethyl‐5‐oxohexyl) phthalate (MEOHP), were related to AGD in infants (Table ). In a study on rats, animals fed 750 mg kg −1 day −1 between gestation days 13 and 20 showed significant reduction in AGD ( P = 0.001) . AGD was significantly correlated with penile width ( r = 0.31, P < 0.05) and penile length ( r = 0.16, P ≈ 0.05) .…”
Section: The Plasticizer Adulteration Incident In Taiwanmentioning
confidence: 99%
See 1 more Smart Citation
“…As a common environmental pollutant, the negative effects of in uterus DEHP exposure on male reproduction have been extensively demonstrated in numerous studies in rodent and humanity (Axelsson et al, ; Ungewitter et al, ). In male rodents, the testicular injuries involve reduction in testis weights and anogenital distance (AGD), decrease in number of spermatogenic cells layers and the sperm density, reduced sperm motility, and disability in fertility (Do, Stahlhut, Ponzi, Saal, & Taylor, ; Grande et al, ; Jones, Boisvert, Francois, Zhang, & Culty, ; Kita et al, ). Besides, DEHP exposed in uterus also lead to the production of hypospadias and cryptorchidism (J. Chen et al, ; Skakkebaek, Rajpertde, & Main, ).…”
Section: Introductionmentioning
confidence: 99%